The Level of Physical Fitness and Everyday Activities vs. Sensory Integration Processing Disorders in Preschool Children – Preliminary Findings - Kosiecz, Anna; Taczała, Jolanta; Zdzienicka-Chyła, Agnieszka; Woszczyńska, Małgorzata; Chrościńska-Krawczyk, Magdalena (Journal of Education, Health and Sport, 2019)
Introduction: Sensory integration processing is defined as organization and interpretation of stimuli reaching the organism. The correctly functioning nervous system interprets sensory impressions, which enables development of awareness of one’s own body and of the surrounding environment. Sensory processing disorders can have a significant impact on the child’s functioning. Aim: The objective of the research was to answer the question whether sensory integration processing disorders in preschool children have an influence on their physical fitness and everyday activities. The research covered a group of 60 preschool children. The studied group comprised 30 children with diagnosed sensory processing disorders, while the control group consisted of 30 children with no disorders diagnosed. Results: The results achieved demonstrate lower physical fitness of children from the studied group and problems with performing everyday activities. The tasks connected with speed and agility were the most problematic. Among everyday activities, the most difficult were: cycling, ball catching, getting dressed and descending stairs. Knowledge of sensory integration processing disorders helps understand problems in the child’s functioning and provides an opportunity to intervene in the form of the sensory integration therapy.